Tinjauan Sistem Keamanan Rekam Medis Elektronik di Rumah Sakit AL Dr. Mintohardjo Jakarta - Aldo Rizky Mahendra; Siswati Siswati; Dina Sonia; Muhammad Fuad Iqbal (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Medical records are important documents that capture the entire medical history of patients, including identification, diagnosis, treatment, and recovery. With advancements in information technology, electronic medical records (EMR) have emerged as a solution to enhance the efficiency and accuracy of patient data management. However, despite the many benefits of EMR, its implementation at AL dr. Mintohardjo Hospital remains hybrid, combining manual and electronic methods. This indicates challenges in transitioning to a fully digital system. This study aims to identify and analyze issues related to the security of EMR at AL dr. Mintohardjo Hospital. Several issues identified include a lack of training for medical record staff regarding cybersecurity practices and data input errors. The research employs a qualitative approach, with data obtained from observations and interviews with hospital stakeholders. The informants in this study include IT staff, medical staff, and administrative staff. The findings regarding the security of electronic medical records (EMR) at AL dr. Mintohardjo Hospital indicate that, although there are established Standard Operating Procedures (SOP) for EMR security, their implementation is still not fully compliant. In terms of confidentiality, integrity, and availability of data, the study found that AL dr. Mintohardjo Hospital has implemented several security measures, such as user authentication and access management. However, weaknesses remain, such as a lack of user awareness regarding regular password changes and excessive access by administrative staff. Additionally, frequent data input errors can lead to serious consequences for patients, and threats to data confidentiality, integrity, and availability. Although the hospital has implemented measures such as firewalls and audit trail systems to protect data, challenges such as unstable internet connections and reliance on a single resource remain concerns. Overall, while the existing security measures are fairly adequate, this study emphasizes the need for improved staff training and strengthened procedures to minimize risks to the security of electronic medical record data.